Hudson Bay Company, Fort Shepherd (1858)
Constructed in the closing years of the fur trade in 1857 as an outpost for the Hudson Bay Co. The post was temporarily closed from 1860 to 1863 then reopened until 1870, when it closed permanently. The buildings burned to the ground in 1872.